1997
DOI: 10.3354/meps151165
|View full text |Cite
|
Sign up to set email alerts
|

Use of natural and created Spartina alterniflora salt marshes by fishery species and other aquatic fauna in Galveston Bay, Texas, USA

Abstract: We compared densities of nekton and infauna among 5 natural and 10 created (3 to 15 yr in age) salt marshes ~n the Galveston Bay system of Texas to test whether these marshes were funct~onally equivalent. Decapod crustaceans dominated the nekton on the marsh surface during both the spnng and the fall. Densltles of daggerblade grass shrlmp Palaemonetes pugio, the most abundant decapod, were not signif~cantly d~fferent among marshes, but the size of these s h r~m p In created marshes was significantly smaller th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(98 citation statements)
references
References 40 publications
3
93
2
Order By: Relevance
“…Zimmerman et al (1984) surveyed the distribution of Penaeus aztecus and found higher densities of prawns in the inner (landward) zone of the salt-marsh habitat. Minello & Webb (1997) found lower densities of P. aztecus and P. setiferus in artificially created marshes than in natural marshes but suggested that the differences might be because the artificial marshes were on higher ground and therefore were inundated for a shorter time. The prawn densities were higher in the natural, more frequently inundated salt marshes.…”
Section: Other Intertidal Habitatsmentioning
confidence: 91%
“…Zimmerman et al (1984) surveyed the distribution of Penaeus aztecus and found higher densities of prawns in the inner (landward) zone of the salt-marsh habitat. Minello & Webb (1997) found lower densities of P. aztecus and P. setiferus in artificially created marshes than in natural marshes but suggested that the differences might be because the artificial marshes were on higher ground and therefore were inundated for a shorter time. The prawn densities were higher in the natural, more frequently inundated salt marshes.…”
Section: Other Intertidal Habitatsmentioning
confidence: 91%
“…the edge effect) by comparing animal densities in Scirpus marsh and inner Spartina alterniflora marsh. Although others have examined the edge effect within S. alterniflora marsh (Peterson & Turner 1994, Minello et al 1994, Minello & Webb 1997, elevation and proximity to marsh edge were confounded in these studies. Elevation within a S. alterruflora marsh generally increases with distance from the shoreline.…”
Section: Discussionmentioning
confidence: 99%
“…When ecosystems are driven through thresholds of undesirable states, losses can be long-lasting or even permanent (Scheffer, 2001;Hawkins et al, 2002). Our present ability to restore habitats is very much in question (Minello and Webb, 1997;Zedler, 2000), and opportunities for restoration can be extremely expensive or even impossible (Costanza et al, 1997). For example, many of the problems of erosion and flooding along European coastlines arise from the destruction of the natural features of the coast that act as sediment stores (e.g.…”
Section: What Is An Environmental Impact?mentioning
confidence: 99%